Validation of diabetes mellitus patient behavior questionnaire in primary health care service - Ginanjar Zukhruf Saputri; Akrom Akrom; Haafizah Dania; Okta Muthia S (Intelektual Pustaka Media Utama, 2019)
This study aimed to develop and validation a questionnaire as measurement instrument for knowledge and adherence behavior of DM patients in primary health care. Cross sectional study design was conducted in diabetes mellitus patient. Inclusion criteria were patients in the age group 18-65 years, diagnosed with DM, receiving at least one oral antidiabetic medication. Questionnaire questions for behavioral item were developed based on Diabetes Mellitus management guidelines and references to previous studies. Evaluation and validation by expert was carried out on diabetes mellitus experts and clinical psychologists. The pilot study was conducted on 10 healthy patients and 10 patients with diabetes who enrolled inclusion criteria. Questionnaire validation test was conducted with 41 DM outpatient at PKU Muhammadiyah Hospital in Yogyakarta. Collecting data by interviewing patients based on questionnaire. Statistical analysis was performed using SPSS with Pearson correlation coefficients for validation test and Cronbach alpha coefficients for reliability test of the questionnaire. Adherence behavior questionnaire consists of 12 question items, which are divided into three domains: cognitive, affective, and psychomotor domains. Validation results showed 12 valid items where the pearson correlation value was>0.308 (n=41). Cronbach alpha as reliability test results showed 0.78. This result showed a questionnaire were valid and reliable in Diabetes Mellitus patients. This instrument would be use in primary health care for measuring adherence behavior of DM patients.